Effect of size heterogeneity on the growth and production economics of African Catfish (Agriculture, Food, and Natural Resources Journal, 2024)
This study aimed to evaluate the impact of size heterogeneity on the growth and production economics of African Catfish (Clarias gariepinus). The experimental fish were divided into two treatment groups - homogenous and heterogonous - with different feeding time intervals morning hour (08.00am) afternoon hour (1:00pm) and evening hour (6:0pm) respectively. Each treatment had two replicates with 20 fish per replicate.  The fish were fed with a commercial feed (coppens) at 5% for 8 weeks and 3% (for 8 weeks) of their body weight to the end of the experiment. The results showed significant differences (p
Keywords: Interactive effect; Length-weight relationship; Nutrient utilization; Profitability